Labour Market in Baltic Countries - the Current Condition and Prospects of Changes - Balcerowicz-Szkutnik, Maria (Rynek pracy państw nadbałtyckich - stan obecny i perspektywy zmian, 2010)
The paper includes analyses concerning genera/ion 50+. The minute analyses are related to the parameters that characterise the labour market, their dynamics in the recent years as well as the forecasts of values for the nearest years. The basis of these analyses are the time series of values of relevant coefficients, derived from Eurostat data base - one of the most credible source of data, or the coefficients that have not been published in any data sources but have been determined on the basis of the age structure of population. The scope of analyses includes not only Poland but also other EU countries. The group of analysed countries involves Baltic countries; it means Poland, Lithuania, Latvia, Estonia, Denmark, Sweden, Finland and Germany. The selection was not random. First four countries are the countries newly admitted into European Union in 2004. The next four countries are the so called 'old' European Union countries, where the functioning of the social system is considered to be more employee-friendly and, consequently, the position of employees of generation 50 + on the labour market may differ from the position of employees in the countries regarded as new in the EU. With regard to the unavailability of some data, the period of analysis includes years 200-2008 and the coefficients which have been found the most important for the evaluation of the labour market condition are: the coefficient of occupational activity, the employment rate, unemployment rate as well as the long-term unemployment rate.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 9-26
Keywords: labour market; employment rate; unemployment rate; long-term unemployment rate